Pralatrexate experience in peripheral T-cell lymphoma: A multicenter retrospective study from Turkey - Dal, Mehmet Sinan; Merdin, Alparslan; Erkurt, Mehmet Ali; Ekinci, Ömer; Albayrak, Murat; Hacıoglu, Sibel Kabukcu; Altuntas, Fevzi (Zerbinis Publications, 2021)
Purpose: Pralatrexate is a new generation antifolate treatment agent used for the treatment of relapsed or refractory peripheral T-cell lymphomas. This study aims to determine the general characteristics of the patients receiving pralatrexate therapy in Turkey, contributing to the literature on the effectiveness of pralatrexate therapy in peripheral T-cell lymphomas by determining the response levels of such patients to the therapy. The study also attempts to clinically examine the major side effects observed in patients during treatment with pralatrexate. Methods: The study included patients with peripheral T-cell lymphoma followed up in the hematology units of several hospitals in Turkey. Overall, 20 patients aged 18 and over were included in the study. Results: The median age at the time of diagnosis was 58.5 years. PTCL-NOS (Peripheral T-cell lymphoma, not otherwise specified) subtype was in 40% of patients, making the PTCL-NOS the most common subtype in the study. In general, most patients were diagnosed with disease at an advanced stage. Pralatrexate therapy was given to the patients at a median treatment line of 3.5. Pralatrexate dose reduction was required in only 3 patients (15%). Response to pralatrexate therapy with partial remission (PR) and above was observed in 11 (55%) of the patients. Conclusion: Pralatrexate seemed to be a promising novel treatment in relapsed refractory PTCL patients. However, patients receiving pralatrexate should be followed up carefully for skin reactions, mucosal side effects, thrombocytopenia and neutropenia. © 2021 Zerbinis Publications. All rights reserved.
Keywords: Multicenter; Peripheral T-cell lymphoma; Pralatrexate